Psychometric Properties of General Self-Efficacy (GSE) Scale Korean Version for Older Korean Immigrants with Diabetes: A Cross-Sectional Study in the United States - Jung Eun Kim; Ying-Hong Jiang; Vivien Dee (MDPI AG, 2023)
Patients with diabetes must have self-efficacy to perform necessary self-care tasks. Self-efficacy has been considered as one of the primary motivators on diabetes self-care; therefore, it is essential for health care professionals to assess the self-efficacy of patients with diabetes to provide optimal care. Despite older Korean immigrants having greater difficulty in diabetes management, research on self-efficacy for them is lacking. This study aims to examine the psychometric property of the General Self-Efficacy scale Korean version for older Korean immigrants with diabetes in the United States. In this cross-sectional, methodological study, data were collected using convenience sampling. Cronbach's alpha, exploratory factor analysis, and confirmatory factor analysis were employed to examine the psychometric properties. Cronbach's alpha for the entire GSE scale Korean version is 0.81. The initial Eigenvalues show two factors, coping and confidence; however, the confirmatory factor analysis showed reasonable goodness of fit to the data (χ2(35) = 86.24, p < 0.01), χ2/df ratio = 2.46, AGFI = 0.87, GFI = 0.91, IFI = 0.90, ECVI = 0.74, CFI = 0.89, and RMSEA = 0.093 in the one-factor model. The General Self-Efficacy scale Korean version demonstrated acceptable reliability and validity. It can be used to investigate self-efficacy and to devise culturally tailored diabetes interventions.